Análisis de las diferencias en la base contable y en la base fiscal por el reconocimiento y medición de los inventarios bajo NIIF. Aplicación del impuesto diferido (2017)
By the importance of inventories in companies (commercial, services, extractive or transformation) and their effect on the financial statements, it is important to understand the recognition and measurement of the accounting base under the new regulatory frameworks and the fiscal base of agreement. to tax regulation, to determine the cost of inventories.The International Financial Reporting Standards (IFRS), mark the independence between the accounting and fiscal regulations, with the tax reform  law 1819 of December 2016, the tax administration issues the tax bases that must be taken into account as of 1 January 2017, harmonizing taxation with the accounting technique and establishing the guidelines for its reconciliation in cases where the tax treatment differs from the accounting technique. The document conducts a study of the differences between the recognition and measurement of Inventories in accordance with IFRS and tax regulations, as well as the tax exceptions to the alternatives for measuring the accounting technique and the application of the deferred tax in accordance with the NIIF when you require it.